Efficient laser-driven proton and bremsstrahlung generation from cluster-assembled foam targets. (9th September 2021) - Prencipe, Irene; Metzkes-Ng, Josefine; Pazzaglia, Andrea; Bernert, Constantin; Dellasega, David; Fedeli, Luca; Formenti, Arianna; Garten, Marco; Kluge, Thomas; Kraft, Stephan; Garcia, Alejandro Laso; Maffini, Alessandro; et al.
Abstract: The interaction between intense 30 fs laser pulses and foam-coated 1.5 μ m-thick Al foils in the relativistic regime (up to 5 × 10 20  W cm −2 ) is studied to optimize the laser energy conversion into laser-accelerated protons. A significant enhancement is observed for foam targets in terms of proton cut-off energy (18.5 MeV) and number of protons above 4.7 MeV (4 × 10 9 protons/shot) with respect to uncoated foils (9.5 MeV, 1 × 10 9 protons/shot), together with a sixfold increase in the bremsstrahlung yield. This enhancement is attributed to increased laser absorption and electron generation in the foam meso- and nanostructure.